2020
DOI: 10.1186/s40623-020-01152-y
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic changes in groundwater level during the 2018 Hokkaido Eastern Iburi earthquake

Abstract: Six wells were continuously monitored in Hokkaido, northern Japan, to relate groundwater level changes to regional seismic activity. Groundwater level changes following the 2018 Hokkaido Eastern Iburi earthquake were detected in three of the six wells, even though they are located hundreds of kilometers from the epicenter. The groundwater level changes are qualitatively consistent with the volumetric strain induced by the earthquake. We analyzed groundwater level responses to the M 2 tidal constituent before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Zhou et al [13] analyzed the mechanism of regional landslides and the stability and permanent displacement of slopes based on the effects of continuous heavy rainfall and seismic motion. Shibata et al [14] reported changes in groundwater levels based on the responses of the groundwater level to the M2 tidal constituent before and after the earthquake. Kubo et al [15] investigated the source rupture process of an earthquake in Japan and reproduced the overall ground motion characteristics of the sedimentary layers of the Ishikari Lowland.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [13] analyzed the mechanism of regional landslides and the stability and permanent displacement of slopes based on the effects of continuous heavy rainfall and seismic motion. Shibata et al [14] reported changes in groundwater levels based on the responses of the groundwater level to the M2 tidal constituent before and after the earthquake. Kubo et al [15] investigated the source rupture process of an earthquake in Japan and reproduced the overall ground motion characteristics of the sedimentary layers of the Ishikari Lowland.…”
Section: Introductionmentioning
confidence: 99%
“…2. Постсейсмическое снижение уровня в скважине Jiangyou при землетрясении Венчуань 12.05.2008 г., М7.9, на врезке -данные прецизионного мониторинга [Liao et al, 2015] В промежуточной зоне, которая определяется эпицентральным расстоянием, составляющим от 1 до 10 длины разлома, и дальней, на эпицентральных расстояниях более 10 длины разлома, гидрогеологические отклики в флюидонасыщенных коллекторах изменяются в широких пределах от первых сантиметров до десятков [Lee et al, 2012;Shi et al, 2014;Shibata et al, 2020;Liu et al, 2023]. В частности, при землетрясении в Пакистане 24.09.2013 г., М7.7 в скважинах, расположенных на эпицентральных расстояниях ~ 3000 км в Израиле, прослежены различные гидрогеологические эффекты.…”
Section: гидрогеологические отклики на землетрясенияunclassified
“…Seismic waves often change the permeability and storage properties of an aquifer system. Therefore, these properties can be estimated from the amplitude responses and phase shifts of tidal components of the groundwater level [8,15,64]. Thus, temporal variations in the tidal constants might reflect changes in aquifer hydraulic properties.…”
Section: Tidal Analysismentioning
confidence: 99%